Anti-neoplastic chemotherapy in children and oral health – review of literature - Krasuska-Sławińska, Ewa; Olczk-Kowalczyk, Dorota (Journal of Stomatology, 2015)
Chemotherapy is one of the most effective neoplasm treatments in children and adolescents. However, anti-neoplastic chemotherapeutics are nonselective and therefore also damage healthy cells, especially those with a high mitotic index, and present a low therapeutic index. Chemotherapy may therefore lead to numerous complications manifesting themselves, among others, in the oral cavity. The study is to present the current state of knowledge on early and late oral complications of anti-neoplastic chemotherapy. Early chemotherapy complications, occurring during treatment or shortly after, mainly include mucositis, infections and bleeding of oral mucosa, salivary gland disorders, taste disorders, painful masticatory apparatus and its functional disorders resulting from drug neurotoxicity. Caries is an early complication, however its risk may remain high even many years after anti-neoplastic treatment completion. Late complications, occurring months or even years after chemotherapy is completed, include congenital tooth anomalies and malocclusions.